Pengembangan Objek Wisata Pantai Batu Pinagut Kecamatan Kaidipang Kabupaten Bolaang Mongondow Utara - Nerli Siki; Meyko Panigoro; Roy Hasiru (Universitas Negeri Gorontalo, 2022)
This study aims to determine the strategy for developing Batu Pinagut Beach tourism objects in Kaidipang District, North Bolaang Mongondow Regency. The data used are sourced from the tourism office of North Bolaang Mongondow Regency and questionnaires. The method used is SWOT analysis. The results of the research on the development of tourism objects on Batu Pinagut Beach in North Bolaang Mongondow Regency resulted in the following conclusions: the government's strategy in developing Batu Pinagut Beach tourism objects was realized by collaborating with the aim of promoting Batu Pinagut Beach tourism, building facilities and infrastructure in Batu Pinagut Beach tourism, as well as carrying out tourism events at Batu Pinagut Beach. In the development of the Batu Pinagut Beach tourist attraction, currently there has been a fairly good increase. These developments have an impact on the economic conditions of the community such as: opening up employment opportunities for the community, increasing people's income. The SWOT approach is used as a method that has many advantages over other approaches, namely with SWOT analysis, it can find out the situation of a tourist attraction by identifying external factors and internal factors that affect tourism objects, namely analyzing the opportunities and strengths they have to determine future plans and overcome them. weaknesses and weaknesses by way of future plans and overcome weaknesses by means of improvement plans.